IMPLEMENTASI PERMENPAREKRAF NO. 4 TAHUN 2014 TENTANG STANDAR USAHA BIRO PERJALANAN WISATA PADA PELAKU USAHA BIRO PEJALANAN WISATA HAJI DAN UMROH DI YOGYAKARTA - Dwi Rohani, Elisa; Surya Pradana, Cerry (Jurnal IPTA (Industri Perjalanan Wisata), 2020)
There are not a few travel agencies that move in the field of Hajj and Umrah that do not have business legality, therefore there needs to be supervision and application of business standards for businesses BPW Hajj and Umrah. The business standard of this travel agency not only applies to BPW who are active in inbound and outbound tour packages but this regulation also applies to BPW which focuses on Hajj and Umrah spiritual travel. Even every BPW Hajj and Umrah is required to have a business certificate of travel agency services in order to obtain a permit for The Umrah Ibadah Travel (PPIU). This research will be carried out on BPW Hajj and Umrah who have certified BPW business field in Yogyakarta which aims to see the extent to which standardization of this business can be applied to businesses and what obstacles faced in the application of business standards. This research uses qualitative research method to obtain data and information needed data collection techniques used in this research including Indepth Interview, observation and policy studies. The results of this study showed that the fundamental problems that are addressed by BPW Hajj and Umrah businesses do not have a valid business license, current and adequate, do not have cooperation with outside parties, especially with vendors, often found BPW business which is a cooperation between friends and family members, as well as the lack of socialization of BPW standards to BPW Hajj and Umrah businesses that are more focused on Umrah activities.